Evaluating Integrated Social Studies Learning Programs in Indonesian Middle Schools: An Application of the Stufflebeam Model - Nana Suraiya; Yusrizal Yusrizal; M.Shabri Abdul Majid; Deny Setiawan; Amiruddin Hasan; Ika Apriani Fata (STAI Hubbulwathan Duri, 2024)
Many studies have been conducted to evaluate the nonintegrated approach. Each model claimed to have certain advantages, but the current research used a combined social science learning model called Stufflebeam's CIPP (context, input, process, and product) model, which included input, process, and product components due its comprehensiveness in assessment and students’ interest based. The assessment model appropriate for Integrated Social Studies learning programs in public middle schools because it could fulfil pedagogical aspects for students in schools. The research group included respondents from eight public middle schools, as well as school administrators, 16 instructors, and 350 pupils. Documentation, questionnaires, and tests are examples of data gathering methods. Content validity is tested using expert opinion, construct validity is tested using a limited test and evaluated using Product Moment correlation, and reliability is tested using Cronbach Alpha. The SPSS software is used to perform data analysis methods such as descriptive statistics. 20. The development of a combined social study learning program evaluation model for public middle schools yielded outstanding assessment criteria. The quality of integrated social studies learning inputs includes: teachers’ competence, students’ motivation, and infrastructure, which are all very good categories; the quality of integrated social studies learning processes, which include initial activities, core activities, and closing activities, which are all excellent categories; and product quality (results) integrated social studies learning includes: attitude competencies, knowledge, and skills.